2007
DOI: 10.1088/0957-4484/18/32/325704
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of dielectric strength in nanocomposites

Abstract: In this paper, we report the dielectric breakdown properties of a nanocomposite, a potential electrical insulation material for cryogenic high voltage applications. The material is composed of a high molecular weight polyvinyl alcohol and nanosized in situ synthesized titanate particles. The dielectric breakdown strengths of the filled material samples, measured in liquid nitrogen, indicate a significant increase in their strengths as compared to unfilled polyvinyl alcohol. We conclude that nanometre-sized par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 17 publications
1
68
0
Order By: Relevance
“…The keystone for tailoring the structure-property of these composites is to understand the effect of the fillers in the electrical, thermal and mechanical properties of the samples. Towards this direction several investigations have been performed on different polymer matrices and filler types and geometries [2][3][4][5][6][7][8][9]. Unambiguously, the dispersion of the fillers is intrinsically related to the performance of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The keystone for tailoring the structure-property of these composites is to understand the effect of the fillers in the electrical, thermal and mechanical properties of the samples. Towards this direction several investigations have been performed on different polymer matrices and filler types and geometries [2][3][4][5][6][7][8][9]. Unambiguously, the dispersion of the fillers is intrinsically related to the performance of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations on composites have shown that the electrical insulation reliability of composites fabricated with nanoparticles (nanodielectrics) is better than that of unfilled matrix materials or composites fabricated with micrometre-size particles [1][2][3][4][5][6]. These new materials have potential for fusion energy and low-temperature power applications, where superconducting wires are employed, since the number of commercially available structural composites with good electrical insulation properties are few [7,8].…”
mentioning
confidence: 99%
“…In conventional polymeric composites for electrical insulation, addition of micrometre size particles degrade dielectric performance of the insulation compared to unfilled polymer. However, no degradation in electrical properties, such as dielectric breakdown, with respect to time and electrical aging of electrical insulation properties has been observed in nanodielectrics for conventional applications [1] and for cryogenic applications [3,[8][9][10]. Although it is clear that nanoparticles influence the dielectric performance, yet no detailed analysis has been performed on the particle size to breakdown strength statistics.…”
mentioning
confidence: 99%
See 2 more Smart Citations